PENGARUH SISTEM PELATIHAN DAN PENGEMBANGAN SDM DALAM MENINGKATKAN PRODUKTIVITAS KARYAWAN DI PT. PLN (PERSERO) UPT PALEMBANG - Maharani, Agista; Agustian, Wiwin (Ensiklopedia of Journal, 2025)
The purpose of this study is to analyze the influence of the HR training and development system in increasing employee productivity, the object of the study was conducted at PT PLN (Persero) UPT Palembang. The sample of this study was 70 employees at PT PLN (Persero) UPT Palembang, the method used was a quantitative method with SPSS analysis techniques. through total sampling techniques. Data collection techniques were carried out by distributing Likert-scale questionnaires. Data analysis included validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and coefficients of determination. The results of the study indicate that the training system has a significant negative effect on employee productivity, with a t-value of -3.244 (p = 0.002). Human resource development shows that organizational culture has a positive effect on employee productivity, with a t-value of 4.593 (p = 0.000). Overall, although the training system does not have a significant partial effect, based on the simultaneous test (F test), both independent variables together have a significant effect on employee productivity (F count = 10.840 > F table = 3.134; Significant 0.000). This indicates that the combination of an effective training system and human resource development strategy still plays a significant role in driving productivity, although the dominant contribution comes from training factors. These findings provide input for the management of PT PLN (Persero) UPT Palembang to prioritize improvements and optimization of the training system, while conducting a comprehensive evaluation of human resource development programs to make them more relevant, measurable, and have a direct impact on work productivity. Keywords: Training System, Human Resource Development, Employee Productivity